Examining the relationship between triage acuity and frailty to inform the care of older emergency department patients: Findings from a large Canadian multisite cohort study. Issue 1 (January 2020) - Mowbray, Fabrice; Brousseau, Audrey-Anne; Mercier, Eric; Melady, Don; Émond, Marcel; Costa, Andrew P.
ABSTRACT: Background: The 2016 Canadian Triage and Acuity Scale (CTAS) updates introduced frailty screening within triage to more accurately code frail patients who may deteriorate waiting for care. The relationship between triage acuity and frailty is not well understood, but may help inform which supplemental geriatric assessments are beneficial to support care in the emergency department (ED). Our objectives were to investigate the relationship between triage acuity and frailty, and to compare their associations with a series of patient outcomes. Methods: We conducted a secondary analysis of the Canadian cohort from a multinational prospective study. Data were collected on ED patients 75 years of age and older from eight ED sites across Canada between November 2009 and April 2012. Triage acuity was assigned using the CTAS, whereas frailty was measured using an ED frailty index. Spearman rank and binary logistic regression were used to examine associations. Results: A total of 2, 153 ED patients were analyzed. No association was found between the CTAS and ED frailty index scores assigned to patients ( r = .001; p = 0.99). The ED frailty index was associated with hospital admission (odds ratio [OR] = 1.5; 95% confidence interval [CI] = 1.4–1.6), hospital length of stay (OR = 1.4; 95% CI = 1.2–1.6), future hospitalization (OR = 1.1; 95% CI = 1.05–1.2), and ED recidivism (OR = 1.1; 95% CI = 1.04–1.2). The CTAS was associated with hospital admission (e.g., CTAS 2 v. 5; OR = 6; 95% CI = 3.3–11.4). Conclusion: Our findings demonstrate that frailty and triage acuity are independent but complementary measures. EDs may benefit from comprehensive frailty screening post-triage, as frailty and its associated geriatric syndromes drive outcomes separate from traditional measures of acuity.